2021
DOI: 10.1101/2021.06.01.446623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic block of SARS-CoV-2 infection by combined drug inhibition of the host entry factors PIKfyve kinase and TMPRSS2 protease

Abstract: Repurposing FDA-approved inhibitors able to prevent infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could provide a rapid path to establish new therapeutic options to mitigate the effects of coronavirus disease 2019 (COVID-19). Proteolytic cleavages of the spike S protein of SARS-CoV-2, mediated by the host cell proteases cathepsin and TMPRSS2, alone or in combination, are key early activation steps required for efficient infection. The PIKfyve kinase inhibitor apilimod interferes wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 55 publications
(102 reference statements)
0
29
0
Order By: Relevance
“…Interaction of SARS-CoV-2 spike protein via the receptor-bind domains (RBDs) with the cell receptor ACE2 induces the endocytosis, and enables entry into many different types of cells, including type II alveolar epithelial cells, monocytes and macrophages. Priming and activation of S protein by the transmembrane serine protease (TMPRSS) 2, TMPRSS4, Factor Xa or by cathepsin is needed in order to facilitate cell surface entry, thus enabling the fusion of SARS-CoV-2 virus with the host cells and viral replication [16,17]. It has been shown that SARS-CoV-2 has 10-20 times higher binding affinity to ACE2 than SARS-CoV, which may result in more effective viral transmission through droplets from individuals with COVID-19.…”
Section: Mechanisms Of Sars-cov-2 Invasionmentioning
confidence: 99%
“…Interaction of SARS-CoV-2 spike protein via the receptor-bind domains (RBDs) with the cell receptor ACE2 induces the endocytosis, and enables entry into many different types of cells, including type II alveolar epithelial cells, monocytes and macrophages. Priming and activation of S protein by the transmembrane serine protease (TMPRSS) 2, TMPRSS4, Factor Xa or by cathepsin is needed in order to facilitate cell surface entry, thus enabling the fusion of SARS-CoV-2 virus with the host cells and viral replication [16,17]. It has been shown that SARS-CoV-2 has 10-20 times higher binding affinity to ACE2 than SARS-CoV, which may result in more effective viral transmission through droplets from individuals with COVID-19.…”
Section: Mechanisms Of Sars-cov-2 Invasionmentioning
confidence: 99%
“…Apilimod prevents the infection of cultured cells with Ebola, Marburg and SARS-CoV-2 [ 68 , 69 ]. Based on a large scale screen in mammalian cell lines [ 70 ], as well as several targeted studies [ 71 , 72 , 73 ], apilimod was proposed as a treatment for COVID-19 and is currently undergoing a phase II clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the serine protease becomes a new therapy for the treatment of many diseases, including Alzheimer disease 37 , autoimmunity disease 38 , and even COVID-19 pandemic 39, 40 . The development of specific inhibitor that selectively target EP maybe a strategy to the clinical intervention of pancreatitis 10 .…”
Section: Resultsmentioning
confidence: 99%